Recent Trends in Cloud Radio Access Networks - Iqra Farhat; Fahim Gohar Awan; Umar Rashid; Haris Anwaar; Nadhira Khezami; Ilyes Boulkaibet; Bilel Neji; Frederic Nzanywayingoma (IEEE Access)
Massive surge in mobile data traffic, high power consumption, and limited spectrum availability are the major challenges of existing cellular networks. Industries and academia have conducted many studies and proposed solutions to meet the exploding user demand and minimize the network operators’ expenditures. The cloud radio access network (CRAN) system is a revolutionary change for cellular networks because of its centralized processing, making it a promising option for 5G and future networks beyond the fifth generation (5G). This study is aimed at providing a complete overview of the CRAN architecture and to conduct an in-depth analysis of its performance metrics. Moreover, it provides the first holistic insight into the recent advances in CRAN architecture; integrating CRAN architecture with proven technologies such as massive multiple-input multiple output (MIMO) systems by equipping the transmitter and the receiver with multiple antennas, intelligent reflecting surfaces, unmanned aerial vehicles, integrated sensing and communication, rate splitting method, and energy harvesting. Further, the related research challenges are also discussed, proposing future directions.